2005
DOI: 10.1093/jhered/esi089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microsatellite DNA Markers for the Giant Anteater Myrmecophaga tridactyla

Abstract: The giant anteater (Myrmecophaga tridactyla) is found from Belize and Guatemala to Paraguay and Argentina. Its conservation status is considered vulnerable by IUCN. Here we report the isolation and characterization of six microsatellite loci. Positive loci for (GT)(n) were isolated using a magnetic bead hybridization selection protocol. The number of alleles per locus as well as the heterozygosity and PCR conditions are described. These loci will be useful for studying population structure, genetic diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…Additionally, for three loci (MtriUSP11, MtriUSP13 and MtriUSP17) the number of alleles per locus found in our sample was lower than the number found by Garcia et al (2005). This may have been due to differences in the sampling distribution between the two studies, because while our study focused on the genetic structure of one population in Emas National Park (ENP) Garcia et al studied the polymorphism of loci and sampled only seven M. tridactyla in ENP and eight from other localities, including animals killed on roads far away from ENP.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Additionally, for three loci (MtriUSP11, MtriUSP13 and MtriUSP17) the number of alleles per locus found in our sample was lower than the number found by Garcia et al (2005). This may have been due to differences in the sampling distribution between the two studies, because while our study focused on the genetic structure of one population in Emas National Park (ENP) Garcia et al studied the polymorphism of loci and sampled only seven M. tridactyla in ENP and eight from other localities, including animals killed on roads far away from ENP.…”
Section: Discussioncontrasting
confidence: 86%
“…Five M. tridactyla (Mtri) microsatellite loci (MtriUSP04, MtriUSP07, MtriUSP11, MtriUSP13) MtriUSP17) previously developed by Garcia et al (2005) were used to genotype all the animals sampled. For genotyping, microsatellite amplifications were performed in a 10 μL volume containing 10.0 μM of each primer, 1 unit of Tax DNA polymerase (Finedraw, BR), 200 μM of each dNTP, 1X reaction buffer (10 mM Tris-HCl, pH 8.3, 50 mM KCl, 1.5 mM MgCl 2 ), and 20 ng of template DNA.…”
Section: Genetic Analysismentioning
confidence: 99%
“…No artifacts or stutter peaks negatively affected the differentiation between homozygote and heterozygote, and the alleles exhibited well‐resolved peaks. The fragments were larger in size relative to the size of the original markers due to the addition of the use of the M13‐tailed primer, but the sizes corresponded to the expected sizes based on the information available on their development (Garcia et al., 2005).…”
Section: Methodsmentioning
confidence: 91%
“…Six pairs of microsatellite‐specific oligonucleotides were used in the molecular analyses, as detailed in Table 1 (Garcia et al., 2005). Genomic DNA was extracted using the QIAmp DNA kit (Qiagen) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…(2007) performed a population genetic study with individuals from the National Park of Emas, one of the largest populations of the species in Brazil (Miranda et al , 2006), using five microsatellite loci previously described by Garcia et al (2005). The study revealed a marked inbreeding within the population, associated to low levels of polymorphism in all loci.…”
Section: Introductionmentioning
confidence: 99%